2021
DOI: 10.1038/s41598-021-83991-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammaging markers characteristic of advanced age show similar levels with frailty and dependency

Abstract: The improvement of life quality and medical advances has resulted in increased life expectancy. Despite this, health status commonly worsens in the last years of life. Frailty is an intermediate and reversible state that often precedes dependency and therefore, its identification may be essential to prevent dependency. However, there is no consensus on the best tools to identify frailty. In this sense, diverse molecules have been proposed as potential biomarkers. Some investigations pointed to an increased chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 49 publications
2
47
1
Order By: Relevance
“…This chronic systemic inflammation is most notably driven by elevated pro‐inflammatory cytokines in the circulation. IL‐6, for example, is normally low or non‐detectable in healthy young adults, but dramatically increased in the blood of individuals over 70 years 261 . Interestingly, splenic stroma obtained from aged mice produces more IL‐6 in vitro compared to stroma from younger mice, as stated in the previous section 240 .…”
Section: Emerging Questions: Macrophage‐fibroblast Circuits In the Aged Spleenmentioning
confidence: 73%
“…This chronic systemic inflammation is most notably driven by elevated pro‐inflammatory cytokines in the circulation. IL‐6, for example, is normally low or non‐detectable in healthy young adults, but dramatically increased in the blood of individuals over 70 years 261 . Interestingly, splenic stroma obtained from aged mice produces more IL‐6 in vitro compared to stroma from younger mice, as stated in the previous section 240 .…”
Section: Emerging Questions: Macrophage‐fibroblast Circuits In the Aged Spleenmentioning
confidence: 73%
“…Systemic inflammation, and a high concentration of IL-6 and TNFα in particular, not only reduces albumin synthesis but also increases its degradation and promotes its transcapillary leakage. Decreased plasma albumin has been considered as a risk factor for nutritional deficiencies and frailty in the elderly [48,49]. Onem et al [49] showed the relationships between albumin concentration and cognitive and motor functions in patients from nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is associated with increased levels of circulating cytokines and proinflammatory markers [27]. According to research, aging is linked to a state of persistent low-grade inflammation and elevated serum levels of inflammatory markers such as IL-6, CRP, and TNF, a process known as "inflammaging" [28].…”
Section: Age and Sexmentioning
confidence: 99%
“…Aging increased serum levels of IL-6, CRP, and TNF-α; women have CRP levels higher than men [27,28,32,35,36,38] Obesity Obese people had significantly higher levels of CRP, TNF-α, and IL-6 than non-obese people. [43,44] Epidemiological factors…”
Section: Age and Sexmentioning
confidence: 99%